Journeys of Identity Construction After Traumatic Brain Injury: Elite Athletes Perform Their Stories of Healing - Smith, Claire (University of Ottawa (Canada), 2010)
It takes time and effort for individuals to construct their identities after a traumatic brain injury. As a former elite athlete who sustained a head injury in 1997, I was interested in listening to the stories told by other former elite athletes who had also suffered head injuries. The purpose of this autoethnographic study was to explore how these athletes have constructed their identities after such a life-altering event. I asked: When elite athletes sustain traumatic brain injuries, what do the athletes' performances reveal about their journeys of identity construction? To collect data, I listened to four athletes' stories, two of whom, like myself, are Olympians, and two are former professional athletes. I talked to each of the athletes over four consecutive days, carefully observing their performances as they told me stories about their lives as athletes, their accidents, their journeys of recovery after their head injuries, and their lives now. On these four days, the athletes took photos with a digital camera to illustrate their perceptions of the lives they now live. I composed illness narratives from my observations, the athletes' performances, and their photos. These illness narratives were then analysed using a lens composed of Riessman's dialogic/performance analysis and Goffman's dramaturgy. The illness narratives and their analyses provide an in-depth study of these athletes' lives after head injury. The analysis revealed that the athletes, unsurprisingly, are still performers, their identities continue to evolve, and that, for the most part, they are comfortable coping with the consequences of their head injures and content with their current lives. My hope is that these stories and the study of them offer inspiration for all survivors of head injury and their supporters.
Keywords: Health Sciences, Rehabilitation and Therapy.; Education, Physical.; Education, Educational Psychology.